Congenital dysfibrinogenemia in a Japanese family with fibrinogen Naples (BβAla68Thr) manifesting as superior sagittal sinus thrombosis. Issue 7 (October 2017) - Yoshida, Satoru; Kibe, Tetsuya; Matsubara, Risa; Koizumi, Shin-ichiro; Nara, Kenji; Amano, Koji; Okumura, Nobuo
Abstract : N/A: Congenital dysfibrinogenemia refers to the presence of a dysfunctional fibrinogen molecule, typically because of mutations in the fibrinogen gene. About 20% of fibrinogen gene mutations are responsible for thrombosis. Here, we described the case of a 17-year-old Japanese boy, who had a sudden stroke because of superior sagittal sinus thrombosis associated with dysfibrinogenemia. Genetic testing confirmed the presence of homozygous fibrinogen Naples (BβAla68Thr) mutation, which was previously reported as a causative mutation for thrombotic dysfibrinogenemia only in an Italian family. In this Japanese family, the patient's 12-year-old asymptomatic sister was also homozygous for this mutation. She, like her brother, was started on warfarin therapy. This report highlights the occurrence of fibrinogen Naples that has caused severe thrombotic complications in a young member of a Japanese family.